Efektivitas Penggunaan Media Tiga Dimensi Dalam Meningkatkan Kemampuan Mengenal Benda pada Siswa Tuna Netra - Restu Wibawa (Jurnal Paedagogy, 2018)
Blindness is a disturbance that occurs in a person's vision, in the form of complete or partial blindness, resulting in malfunctioning of vision. The difficulty in recognizing objects in blind students is due to the lack of media used in the learning process, the media used must be in accordance with the deficiencies experienced by students, namely not being able to see objects but requiring media that can be touched directly by students. Therefore we need media that can support the learning process in this case, namely three-dimensional media. The formulation of the problem of this research is whether there is an effectiveness of using three-dimensional media in increasing the ability to recognize objects for blind students. While the aim is to determine the effectiveness of using three-dimensional media in improving the ability to recognize objects for blind students. The type of this research is using quantitative descriptive methods. The method used to obtain data in this study is a test method and data analysis method using t-test analysis. Based on the results of the data analysis carried out, before using three-dimensional media from 23 students from 3 classes only 10 students completed and in each class there were 3-4 students who completed after the use of three-dimensional media in the learning process increased student learning completeness. Of the 23 students in 3 different classes 19 students were declared complete with an average grade of 7-8 students, this proved a very significant increase.